Macrophages in bacterial lung diseases: phenotype and functions (review) - E. G. Churina; A. V. Sitnikova; O. I. Urazova; S. P. Chumakova; M. V. Vins; A. E. Beresneva; V. V. Novitskii (Бюллетень сибирской медицины)
This literature review is devoted to the analysis of the role of macrophages in the immunopathogenesis of infectious lung diseases of bacterial etiology. The article summarizes information about the origin of macrophages, their phenotypic and functional heterogeneity. The mechanisms of impaired protective function of innate immunity are associated with the polarization of the program of maturation and activation of macrophages in the direction to tolerogenic or immunoregulatory cells with phenotype of M2. Alveolar macrophages perform a variety of functions (from pro-inflammatory to regenerative) in the development of inflammation in the respiratory organs. Their inherent plasticity suggests that the same macrophages can change their phenotype and function depending on the microenvironment in the inflammatory focus at different stages of the disease. Understanding the mechanisms that regulate macrophage plasticity will be an important step towards realizing the potential of personalized immunomodulatory therapy.